A new failure mode and effects analysis model using Dempster–Shafer evidence theory and grey relational projection method. (November 2018) - Chen, Luyuan; Deng, Yong
Abstract: Failure mode and effects analysis (FMEA) is an important analytical tool in reliability engineering to identify the critical potential failure modes. In this paper, a new FMEA model using Dempster–Shafer evidence theory (DSET) and grey relational projection method (GRPM) is proposed, which mainly manages two critical issues of FMEA: the presentation and handling of various types of uncertainty and the ranking of risk priorities of failure modes. DSET has a good advantage to express and model the assessment results of risk factors. GRPM is used to determine the risk priority order of the identified failure modes, where the double reference points (the positive/negative ideal alternative) are applied. Two illustrative cases are provided to demonstrate the effectiveness and practicality of the proposed method.